Les peintures murales du château de Streversdorp à Montzen - José Vetro (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In June 2012, the wall paintings of theCastle of Streversdorp were investigated with anX-Ray Fluorescencemobile spectrometerbelonging to theEuropean Centre forArchaeometry(Liège).This instrumentprovides information about materials usedin thesemedieval paintings. The interest of the research and otherobservationsthat resultallowsthe developmentofan appropriate methodologyfor a futurerestoration project.